2019
DOI: 10.1002/anie.201911170
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Reactivity of the [P8W48O184]40− Inorganic Ring and Its Assembly into POMZite Inorganic Frameworks with Silver Ions

Abstract: The construction of pure‐inorganic framework materials with well‐defined design rules and building blocks is challenging. In this work, we show how a polyoxometalate cluster with an integrated pore, based on [P8W48O184]40− (abbreviated as {P8W48}), can be self‐assembled into inorganic frameworks using silver ions, which both enable reactions on the cluster as well as link them together. The {P8W48} was found to be highly reactive with silver ions resulting in the in situ generation of fragments, forming {P9W63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…All‐inorganic POM coordination networks, such as those shown in Figure , contain POM clusters connected solely through coordinative O–M–O (where M is generally a transition or lanthanide metal) bonds to form one‐dimensional chains, two‐dimensional sheets or three‐dimensionally connected extended solids . Such materials combine the all‐inorganic nature of zeolites with the coordination linkages of MOFs and thus represent an exciting class of materials for realizing and understanding design principles of tunable, molecule‐based metal oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All‐inorganic POM coordination networks, such as those shown in Figure , contain POM clusters connected solely through coordinative O–M–O (where M is generally a transition or lanthanide metal) bonds to form one‐dimensional chains, two‐dimensional sheets or three‐dimensionally connected extended solids . Such materials combine the all‐inorganic nature of zeolites with the coordination linkages of MOFs and thus represent an exciting class of materials for realizing and understanding design principles of tunable, molecule‐based metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials combine the all‐inorganic nature of zeolites with the coordination linkages of MOFs and thus represent an exciting class of materials for realizing and understanding design principles of tunable, molecule‐based metal oxides. All‐inorganic frameworks based on [P 8 W 48 O 184 ] 40− (denoted {P 8 W 48 }) have recently gained attention and have provided a platform for establishing the assembly motifs accessible with this class of materials . {P 8 W 48 } has been shown to assemble into a diverse array of topologies, but the factors affecting the assembly architecture of these all‐inorganic frameworks are not yet well‐understood.…”
Section: Introductionmentioning
confidence: 99%
“…23,25,26 In 2017, Boyd et al demonstrated how {P 8 W 48 } POMs can additionally be used to construct a species of porous nanomaterial commonly referred to as a POMzite. 26 In these POMzites, individual POMs are linked together by transition metal (TM) oxide anions of the form [MO x ] q−27 (where M = Mn, 28,29 Co, 27 V, 27 Ni, 26 Ag, 30 x = 4−6). The pairing of a rigid structure with a high degree of customizability grants POMzites the capacity to rival similar porous materials, such as zeolites and metal organic frameworks (MOFs); 31 displaying the benefits of both while suffering from the disadvantages of neither.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyoxometalate (POM), a kind of anionic early transition metal oxo cluster, has been the focus attention for researchers based on diverse structures such as, cage, [6] sphere, [7] ring [8] and wheel [9] shape et al and intriguing properties range from catalytic, [10][11] medicine, [12] optics, [13] electricity [14] and magnetism. [15] One of the most outstanding properties of POMs is reversible redox properties, making it an ideal candidate for electrocatalysts or electrode materials.…”
Section: Introductionmentioning
confidence: 99%